Demystification of GM crop costs: releasing late blight resistant potato varieties as public goods in developing countries - Schiek, Benjamin E.; Hareau, Guy; Baguma, Yona K.; Medakker, A.; Douches, D.; Shotkoski, F.A.; Ghislain, M. (Inderscience Publishers, 2016)
A few studies have reported some of the costs associated with bringing to market genetically-modified (GM) crops but no comprehensive studies exist on the real cost of the entire process of developing and releasing one GM variety by a not-for-profit institution in a developing country for sustainable agriculture. Despite the lack of documented studies, it is commonly assumed that such an undertaking is cost prohibitive, based on mere hearsay, and on two private sector cost assessments. The present study assesses the costs and the time expenditures to two not-for-profit programs, one lead by CIP and the other by Cornell University, of developing a late blight resistant (LBr) potato variety for release in one developing country. CIP’s costs run to $1.6 million over eight years, while Cornell’s costs amount to $1.4 million over nine years. Exogenous disturbances might result in insignificant increases in cost, but can increase time expenditure significantly. A sensitivity analysis revealed that the total cost is markedly influenced by technical parameters determining the production and identification of the pre-commercial LBr transgenic event.